2012
DOI: 10.22610/jebs.v4i11.367
|View full text |Cite
|
Sign up to set email alerts
|

Branding in Serbian Rural Tourism

Abstract: To become competitive in the global world market, as a relatively new destination for rural tourism, we need to know how to use existing resources and to prove capable of coping with new challenges. The road to this great accomplishment goes through branding, because only with the help of branding it is possible to achieve recognition of Serbian rural product. That, first, implies a reformatory process of searching for our renewed that is redesigned identity, networking of various industries, as well as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Tourism has long been seen as a path to the sustainability of underdeveloped parts of Serbia [119]. Vukić and Kuzmanović [120] dealt with the issue of rural tourism branding. They suggested that for the Serbian village to become a brand, it must cause a sense of credibility of its own quality.…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…Tourism has long been seen as a path to the sustainability of underdeveloped parts of Serbia [119]. Vukić and Kuzmanović [120] dealt with the issue of rural tourism branding. They suggested that for the Serbian village to become a brand, it must cause a sense of credibility of its own quality.…”
Section: Economic Sustainabilitymentioning
confidence: 99%